2020
DOI: 10.3390/ijms21239295
|View full text |Cite
|
Sign up to set email alerts
|

Spreading of Isolated Ptch Mutant Basal Cell Carcinoma Precursors Is Physiologically Suppressed and Counteracts Tumor Formation in Mice

Abstract: Basal cell carcinoma (BCC) originate from Hedgehog/Patched signaling-activated epidermal stem cells. However, the chemically induced tumorigenesis of mice with a CD4Cre-mediated biallelic loss of the Hedgehog signaling repressor Patched also induces BCC formation. Here, we identified the cellular origin of CD4Cre-targeted BCC progenitors as rare Keratin 5+ epidermal cells and show that wildtype Patched offspring of these cells spread over the hair follicle/skin complex with increasing mouse age. Intriguingly, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…In mice, the absence of macroscopic BCCs has been a major shortcoming of both the conditional Ptch1 -deletion and SmoM2 -overexpression models, confirming that tumors do not progress, regardless of how upstream Hh signaling becomes activated or which Cre driver is utilized ( Brandes et al, 2020 ; Grachtchouk et al, 2003 ; Kasper et al, 2011 ; Mao et al, 2006 ; Peterson et al, 2015 ; Wang et al, 2017 ; Youssef et al, 2010 ). Indeed, previous studies have shown that nascent BCC-like tumors induced by non-targeted Ptch1 deletion similarly regress due to macrophage-induced tumor differentiation ( Nitzki et al, 2010 ).…”
Section: Discussionmentioning
confidence: 90%
“…In mice, the absence of macroscopic BCCs has been a major shortcoming of both the conditional Ptch1 -deletion and SmoM2 -overexpression models, confirming that tumors do not progress, regardless of how upstream Hh signaling becomes activated or which Cre driver is utilized ( Brandes et al, 2020 ; Grachtchouk et al, 2003 ; Kasper et al, 2011 ; Mao et al, 2006 ; Peterson et al, 2015 ; Wang et al, 2017 ; Youssef et al, 2010 ). Indeed, previous studies have shown that nascent BCC-like tumors induced by non-targeted Ptch1 deletion similarly regress due to macrophage-induced tumor differentiation ( Nitzki et al, 2010 ).…”
Section: Discussionmentioning
confidence: 90%